Interpersonal Communication Among Teenagers Through Memes on Discord Media - Kurniawan, Kurniawan; Djalil, Nur Alim; Fitriana, Fitriana (Jurnal Ar Ro'is Mandalika (Armada), 2025)
This study aims to understand teenagers' interpersonal communication patterns through the use of memes on Discord, identify the motivations behind them, and their impact on social relationships. Using a descriptive qualitative approach, data was collected through participatory observation, in-depth interviews, and document analysis on a community of active teenagers on Discord. Informants were teenagers aged 15-19 years old who were active for at least the last three months. The results showed that memes became an effective communication tool to convey humor, symbols, and strengthen social relationships. Discord provides a flexible space to share memes as a creative medium that reflects teenagers' perspectives and experiences. The effectiveness of communication is influenced by content relevance, creativity, and cultural sensitivity. However, challenges such as lack of context understanding, fear of criticism, and content saturation also arise. Good moderation within the group is important to create a safe space that is balanced between freedom of expression and community norms.